Comparison of the Effectiveness of Interventional Endoscopy in Bleeding Peptic Ulcer Disease according to the Timing of Endoscopy (Gut and Liver, 2009)
Background/AimsThe optimal timing for interventional endoscopy in bleeding peptic ulcer disease is controversial. This study compared the outcomes between early endoscopy and delayed endoscopy in patients with bleeding peptic ulcer disease.Methods : We conducted a prospective analysis of data from 90 patients with bleeding peptic ulcer disease who visited the emergency room between May 2006 and September 2007. Patients were categorized into two groups: the early-endoscopy group (admitted during the daytime or at night with prompt endoscopic management) and the delayed-endoscopy group (admitted at night or during weekends, with endoscopic management delayed until the next day). We compared the clinical outcomes of endoscopy between the two groups.Results : There were 49 patients in the early-endoscopy group and 41 patients in the delayed-endoscopy group. Patient demographics, clinical characteristics, bleeding control modality, and Rockall score did not differ between the two groups. There were also no significant differences between the early- and delayed-endoscopy groups in the re-bleeding rate (3/49 vs 5/41, p=0.313), the duration of hospital stay (10.7 vs 9.3 days, p=0.437), and the total amount of blood transfused (3.4 vs 2.7 units, p=0.240).Conclusion : sThe effectiveness of interventional endoscopy for patients with bleeding peptic ulcer disease is not significantly affected by the timing of endoscopy.